Patient eligibility for anti-fibrotic therapy in idiopathic pulmonary fibrosis can be altered by use of different sets of reference values for calculation of FVC percent predicted. (November 2016) - Ward, Katie; Spurr, Lydia; Goldman, Nina R.; Margaritopoulos, George A.; Kokosi, Maria; Renzoni, Elizabetta; Chua, Felix; Maher, Toby M.; Ward, Simon; Wells, Athol U.
Abstract: Antifibrotic drugs for idiopathic pulmonary fibrosis patients in England and Scotland are only available to those with FVC percent predicted (FVC%pred) less than or equal to 80%. The prescribing guidance does not state which set of reference values should be used and we show that a patient's FVC%pred can change by 4–6% depending on the choice of reference. We calculated FVC%pred for a group of 528 IPF patients using three different sets of reference values. 90% of patients with FVC%pred 80–85% calculated using European Community Coal and Steel (ECSC) reference values fall into the eligible range when NHANES reference values are used. Highlights: FVC percent predicted (FVC%pred) can be calculated using different reference values. FVC%pred<80% may determine patient eligibility for antifibrotics in IPF. FVC reference values often used in trials and clinical practice are ECSC, GLI and NHANES. ECSC FVC%pred usually falls by 4–6% when converted to NHANES FVC%pred. Most patients with ECSC FVC%pred 80–85% will have NHANES FVC%pred <80%.